ORIENTASI PASAR DAN INOVASI ORGANISASI DALAM MENINGKATKAN PANGSA PASAR SERTA IMPLIKASINYA PADA PROFITABILITAS (Survei pada Usaha Kecil Menengah/UKM Industri Kerajinan di Kalimantan Tengah) - Hartelina Hartelina (Indonesian Journal of Economics and Business, 2011)
The purpose of is this research is to analyze result; (1) market orientation and innovation in organizations, market share, and SMEs profitability (2) the relationship of market orientation and organizational innovation, (3) the influence of market orientation and organizational innovation to the market share either simultaneously or partial, (4) the influence of market orientation and organizational innovation through the market share to the  profitability on Small and Medium Enterprises (SMEs), partially and simultaneously.This type of research is descriptive and verification. The unit of analysis is the SME handicraft industry with the target population is the SMEs handicraft industry in Central Kalimantan. Sample is 250 from 1650 SMEs Data were analyzed using structural equation model (SEM), given the model is composed of a number of causal relationships between latent variables.The results of this research has relevance in explaining conformity between variables. Its results are: market orientation, organizational innovation, market share and profitability SMEs handicraft industry in Central Kalimantan is on the category not optimal yet. Market orientation and organizational innovation have positive and significant influence, simultaneously and partially to market share, where organizational innovation influence is more dominant. Market orientation, organizational innovation and market share have positive and significant influence to profitability simultaneously and partially, where partially, the influence of market share to profitability is stronger.